Studi Kasus Uji Pra Klinik Perawatan Ulkus Kaki Diabetic Dengan Topikal Hidrokoloid Kunyit - Doddy Yumam Prasetyo; Muhammad Mardiyono; heni Kusuma (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2017)
Diabetic foot ulcers is a chronic complications, which has many long term, can result amputation. Wound care is the one of nursinginterventions effective; principles in wound care are giving a moist and warm environment in order to improve wound healing process.Hydrocolloid turmeric is one of wound treatment moisture balance and can be used as an anti-inflammatory and anti-bacterial. This study aimed to analyze the effect of hydrocolloid turmeric against diabetic ulcer healing process. This research was conducted by case study on 7 respondents, wound care with hydrocolloid tumeric at 21 days. At 7 patient with diabetic foot ulcers were intervention wound care with hydrocolloid tumeric at 21 days, showed score decrease in degree of wound healing, based Betes Jensen Scale.